Mutation of the diamond-blackfan anemia gene Rps7 in mouse results in morphological and neuroanatomical phenotypes - Watkins-Chow, D; Cooke, J; Pidsley, R; Edwards, A; Slotkin, R; Leeds, K; Mullen, R; Baxter, L; Campbell, T; Salzer, M; Biondini, L; Gibney, G; et al. (Public Library of Science, 2013)
The ribosome is an evolutionarily conserved organelle essential for cellular function. Ribosome construction requires assembly of approximately 80 different ribosomal proteins (RPs) and four different species of rRNA. As RPs co-assemble into one multi-subunit complex, mutation of the genes that encode RPs might be expected to give rise to phenocopies, in which the same phenotype is associated with loss-of-function of each individual gene. However, a more complex picture is emerging in which, in addition to a group of shared phenotypes, diverse RP gene-specific phenotypes are observed. Here we report the first two mouse mutations (Rps7(Mtu) and Rps7(Zma)) of ribosomal protein S7 (Rps7), a gene that has been implicated in Diamond-Blackfan anemia. Rps7 disruption results in decreased body size, abnormal skeletal morphology, mid-ventral white spotting, and eye malformations. These phenotypes are reported in other murine RP mutants and, as demonstrated for some other RP mutations, are ameliorated by Trp53 deficiency. Interestingly, Rps7 mutants have additional overt malformations of the developing central nervous system and deficits in working memory, phenotypes that are not reported in murine or human RP gene mutants. Conversely, Rps7 mouse mutants show no anemia or hyperpigmentation, phenotypes associated with mutation of human RPS7 and other murine RPs, respectively. We provide two novel RP mouse models and expand the repertoire of potential phenotypes that should be examined in RP mutants to further explore the concept of RP gene-specific phenotypes.